W.J.T. Mitchell e la nascita dei visual studies 369 Biografie - Merlini, Anita (Scenari, 2021)
This article explores the relationship between visual studies and W.J.T. Mitchell. In particular, we will examine how Mitchell contributed to the development of visual studies and how this contribution prevented visual studies from being recognised as a discipline in all respects. It will be argued that Mitchell’s reflection has certainly established the problems and approaches characterizing visual studies, but he distances himself from this field of study, finally precluding the possibility of their definition and their disciplinary limitation. Therefore, if visual studies really aim at a full acknowledgement, they need to reconsider and to elaborate their own bond to Mitchell.